Is Death a ‘Journey’? The Role of Conceptual Metaphors in Thanatology - MBEY , Etete Gregory; EKI, Margaret Vincent; EDUNG, Augustine A.; EBINGHA, Beatrice N.; ELEKWACHI, Chidimma (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2025)
The conceptualization of death as a “journey” represents a fundamental cognitive framework that permeates linguistic, cultural, and psychological discourses surrounding mortality. This interdisciplinary study employs conceptual metaphor theory (Lakoff & Johnson, 1980) to analyze how journey metaphors structure human comprehension of death across religious, medical, and secular contexts. Through systematic examination of linguistic expressions (“passed away,” “crossing over”), ritual practices, and contemporary digital memorialization, the paper demonstrates how these metaphors serve vital psychological functions in mitigating death anxiety while simultaneously raising philosophical questions about the literalization of figurative language. The analysis reveals three key tensions: between metaphor’s cognitive necessity and its potential to obscure biological reality; between cross-cultural commonalities and specific metaphorical variations; and between traditional journey concepts and emerging digital afterlife frameworks. Drawing on thanatology, cognitive science, and philosophy of language, the study argues for a balanced approach to death discourse that acknowledges metaphor’s constitutive role while maintaining critical awareness of its limitations. The findings have significant implications for palliative care, grief counseling, and public death education in an era of both medicalized dying and technological immortality.